Investigasi Kesenjangan Pengguna Instant Messenger Ditinjau dari Aspek Desain User Interface dan Teknologi - Taufiq Agung Cahyono; Maliatul Fitriyasari; Tias Hafidzotul Luthfiana (G-Tech: Jurnal Teknologi Terapan, 2023)
With the development of instant messenger applications, people began to abandon SMS. This phenomenon has become a momentum for instant messenger application developers to offer features with the latest technology, with the aim of attracting user attention. However, performance improvements are not always in accordance with user needs. In fact, many users prefer instant messenger applications that have standard features. This research discusses the factor analysis of a person in determining the instant messenger application used. The analysis process is carried out by comparing two main variables, namely user interface design and technology used. Data collection was carried out by distributing questionnaires and conducting deep interviews with 80 respondents. The results of this research indicate that user interface design is the main factor in determining a person's use of instant messenger applications.